Twentieth-Century Drawings from the Anderson Collection : Auguste Rodin to Elizabeth Murray (Stanford : Stanford University Museum of Art, 1988)
Rodin, Auguste ; Duchamp, Marcel ; Nadelman, Elie ; Nolde, Emil ; Dove, Arthur ; Marin, John ; Feininger, Lyonel ; Matisse, Henri ; Gonzalez, Julio ; Lipchitz, Jacques ; Moore, Henry ; Motherwell, Robert ; Dubuffet, Jean ; Gorky, Arshile ; Picasso, Pablo ; Baziotes, William ; etc.
Twentieth-Century Drawings from the Anderson Collection : Auguste Rodin to Elizabeth Murray, Stanford University Museum of Art, Stanford, November 15, 1988 - February 19, 1989
boek